2021
DOI: 10.18632/aging.202871
|View full text |Cite
|
Sign up to set email alerts
|

A novel focal adhesion related gene signature for prognostic prediction in hepatocellular carcinoma

Abstract: Hepatocellular carcinoma (HCC) is a highly heterogeneous disease. Reduced expression of focal adhesion is considered as an important prerequisite for tumor cell invasion and metastasis. However, the prognostic value of focal adhesion related genes in HCC remains to be further determined. In this study, RNA expression profiles were downloaded from public databases. A five focal adhesion related gene signature model was established by the least absolute shrinkage and selection operator Cox regression analysis, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…Notably, molecular VM-related DEGs were mainly associated with cell junction, adhesion, and anoikis ( Supplementary Figures S1C, D ). A novel focal adhesion–related gene signature was significantly correlated with tumor grade, tumor stage, immune scores, and immune infiltrate types, according to Lin et al (2021) . Anoikis-resistant mechanically stressed cancer cells exhibited enhanced motility and evaded immune surveillance by natural killer cells, according to Fanfone et al (2022) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, molecular VM-related DEGs were mainly associated with cell junction, adhesion, and anoikis ( Supplementary Figures S1C, D ). A novel focal adhesion–related gene signature was significantly correlated with tumor grade, tumor stage, immune scores, and immune infiltrate types, according to Lin et al (2021) . Anoikis-resistant mechanically stressed cancer cells exhibited enhanced motility and evaded immune surveillance by natural killer cells, according to Fanfone et al (2022) .…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the KEGG and GO enrichment analyses of molecular VM-related DEGs found that they were significantly enriched in focal adhesion and regulation of anoikis. There was a significant association between a novel focal adhesion-related gene signature and tumor grade, tumor stage, immune scores, and immune infiltrate types, determined by Lin et al (2021). It was discovered by Fanfone et al (2022) that anoikis-resistant mechanically stressed cancer cells were more motile and had a better immune response Frontiers in Pharmacology frontiersin.org 13 against natural killer cells.…”
Section: Discussionmentioning
confidence: 99%
“…We found that focal adhesion, aerobic glycolysis, HIF1 transcription factor pathway, IL‐4 and IL‐13 signalling, as well as HSF1 dependent transactivation were markedly enriched in CD8T‐RGPI high‐risk group. Focal adhesion has been shown to mediate the adhesion between tumour cells and extracellular matrix cells, contributing to HCC progression and metastasis 36,37 . Hyperactivity of aerobic glycolysis is prevalent in human carcinomas, and is associated with tumour invasion and HCC poor prognosis 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Focal adhesion has been shown to mediate the adhesion between tumour cells and extracellular matrix cells, contributing to HCC progression and metastasis. 36,37 Hyperactivity of aerobic glycolysis is prevalent in human carcinomas, and is associated with tumour invasion and HCC poor prognosis. 38 Aerobic glycolysis is involved in tumour cell immune escape through various signals, including CD47-ENO1 axis 39 and Notch1/TAZ axis.…”
Section: Discussionmentioning
confidence: 99%